Multifaceted role of SARS-CoV-2 structural proteins in lung injury - Zheng, Guoping; Qiu, Guanguan; Qian, Huifeng; Shu, Qiang; Xu, Jianguo (Frontiers in Immunology, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the third human coronavirus to cause acute respiratory distress syndrome (ARDS) and contains four structural proteins: spike, envelope, membrane, and nucleocapsid. An increasing number of studies have demonstrated that all four structural proteins of SARS-CoV-2 are capable of causing lung injury, even without the presence of intact virus. Therefore, the topic of SARS-CoV-2 structural proteinevoked lung injury warrants more attention. In the current article, we first synopsize the structural features of SARS-CoV-2 structural proteins. Second, we discuss the mechanisms for structural protein-induced inflammatory responses in vitro. Finally, we list the findings that indicate structural proteins themselves are toxic and sufficient to induce lung injury in vivo.Recognizing mechanisms of lung injury triggered by SARS-CoV-2 structural proteins may facilitate the development of targeted modalities in treating COVID-19.